The internet of things vision: a comprehensive review of architecture, enabling technologies, adoption challenges, research open issues and contemporary applications - Olanrewaju, Rashidah Funke; Khan, Burhan Ul Islam; Hassan Abdalla Hashim, Aisha; Sidek, Khairul Azami; Khan Ismail, Zuhani; Daniyal, Hamdan (Akademia Baru Publishing (M) Sdn Bhd, 2022)
With the improvements in machine-to-machine (M2M) communication, ubiquitous computing, and wireless sensor networks, the Internet of Things (IoT) has become a notion that is constantly rising in importance. Using uniquely addressable IDs, the Internet of Things links diverse physical items and allows them to communicate with one another through the Internet. A general overview of the IoT in the context of the architecture and associated technologies is provided in this article. On the other hand, the Internet of Things does not follow a standardised architecture model. This is accomplished by describing widely recognised architectural concepts that are subsequently refined with the associated technology in various tiers. Also included are some solutions that have been developed and future directions for addressing the obstacles faced by the IoT paradigm. Finally, the article discusses several Internet of Things applications to demonstrate the viability of the IoT idea in real-world settings